Quorum Sensing - A Stratagem for Conquering Multi-Drug Resistant Pathogens - Tonkin, Madison; Khan, Shama; Wani, Mohmmad Y.; Ahmad, Aijaz (Current Pharmaceutical Design, 2021)
Quorum sensing is defined as a cell to cell communication between micro-organisms, which enables micro-organisms to behave as multicellular organisms. Quorum sensing enables many collaborative benefits such as synchronisation of virulence factors and biofilm formation. Both quorum sensing, as well as biofilm formation, encourage the development of drug resistance in micro-organisms. Biofilm formation and quorum sensing are causally linked to each other, playing a role in the pathogenesis of the micro-organisms. With the increasing drug resistance against the available antibiotics and antifungal medications, scientists are combining different options to develop new strategies. Such strategies rely on the inhibition of the communication and virulence factors rather than on killing or inhibiting the growth of the micro-organisms. This review encompasses the communication technique used by micro-organisms, how micro-organism resistance is linked to quorum sensing, and various chemical strategies to combat quorum sensing, thereby, drug resistance. Several compounds have been identified as quorum sensing inhibitors and are known to be effective in reducing resistance as they do not kill the pathogens but rather disrupt their communication. Natural compounds have been identified as anti-quorum sensing agents. However, natural compounds have several disadvantages. Therefore, the need for the development of synthetic or semi-synthetic compounds has arisen. This review argues that antiquorum sensing compounds are effective in disrupting quorum sensing and could, therefore be effective in reducing micro-organism drug resistance.
Keywords: quorum sensing inhibitors